Effect of sulphate and blend of plant parts containing secondary metabolites on in vitro methanogenesis, digestibility and feed fermentation with buffalo rumen liquor - GUPTA, V P; KAMRA, D N; AGARWAL, N; CHAUDHARY, L C (The Indian Journal of Animal Sciences, 2017)
A blend of plant parts containing fruit of Phyllanthus emblica (amla), seed of Foeniculum vulgare (fennel) and seed of Trachyspermum ammi (ajwain) mixed in equal proportion (BP) was tested at 0, 10 and 20% of the substrate along with 0, 2.5 and 5% of sodium sulphate (S) for their effects on in vitro methane production and feed fermentation. Inclusion of combination of BP with S did not affect production of total gas, methane and feed digestibility. In vitro gas production was not influenced by any level of S, whereas, it increased linearly with increasing level of BP. Inhibition pattern of methane production (ml/g DM) was similar by inclusion of both S and BP and the inhibition was 21.3% by inclusion of BP20S5. In vitro true digestibility of feed was significantly increased by inclusion of both S and BP and was 10.9% higher with BP20S5 as compared to control (BP0S0). Total volatile fatty acids were not affected by any of the treatments, whereas, acetate was increased and propionate and butyrate were significantly reduced resulting in increased acetate to propionate ratio. Ammonia production was not affected by inclusion of neither S nor BP. It may be summarized that the blend of amla, ajwain and fennel and sodium sulphate can be explored as feed additive to mitigate methane production with an additional benefit of improvement in feed digestibility.